History and Cultural Memory in Neo-Victorian Fiction Victorian Afterimages - Mitchell, Kate (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2010)
A PDF version of this book is available for free in open access via the OAPEN Library platform, www.oapen.org. Arguing that neo-Victorian fiction enacts and celebrates cultural memory, this book uses memory discourse to position these novels as dynamic participants in the contemporary historical imaginary.